Ritter außer Gefecht: Konzepte passiver Bewährung im Wigalois und im Widuwilt - Lembke, Astrid (Aschkenas, 2015)
Wirnt von Grafenberg’s Middle High German romance ›Wigalois‹ features a hero who proves his knightly excellence not only actively when fighting male opponents but also passively when threatened by aggressive women. By killing his most dangerous opponent and burying that opponent’s wife, Wigalois overcomes his passivity and turns into an unquestioned sovereign ruler. The protagonist of the romance ›Widuwilt‹, on the other hand, a late medieval anonymous Yiddish adaptation of Wirnt ’s ›Wigalois‹, is characterized as passive and helpless throughout the text. Instead of overcoming his most dangerous opponent, the hero is overcome himself. Until the very end he depends upon the help of others, especially women. This transformation points to a preference for symmetrical relationships between men and women as well as to a concept of heroism that places the hero within his community instead of apart from it.